Index to Philippine periodicals, 1995-2000 - University of the Philippines (Diliman) Library (Quezon City University Library, UP Diliman, 2001)
The IPP 1995-2000 is a cumulative index to popular and scholarly periodicals published in the Philippines from 1995 to 2000. It consists of bibliographic descriptions of the articles and is searchable by subject and author.
Includes CDS/ISIS 3.08.
Title from disc label.
Also published quarterly in print by the Library.